2011
DOI: 10.1590/s0034-737x2011000100007
|View full text |Cite
|
Sign up to set email alerts
|

Severidade da ferrugem da soja em função do suprimento de potássio e cálcio em solução nutritiva

Abstract: Severidade da ferrugem da soja em função do suprimento de potássio e cálcio em... ) was used. Plants were inoculated at growth stage V4 and after nine days weekly evaluations of disease severity were carried out using percentage of injured tissues, which were transformed into area under the disease progress curve (AUDPCS). Potential photosynthesis and nutrient content in the root, stem and leaf dry matter were also evaluated. The supply of Ca reduced AUDPCS at all doses of K. The supply of K alsoRecebido para … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 11 publications
0
7
0
4
Order By: Relevance
“…However, if not applied in balance with other cations in the soil, it can compete with Mg 2+ , K + and NH 4+ for the same absorption sites, render the plants deficient in these minerals and unbalance plant nutrition. Studies in this line were carried out in coffee (Garcia Junior et al, 2003), soybean (Pinheiro et al, 2011) and corn (Carvalho et al, 2013).…”
Section: Silicon Influence On the Absorption Of Essential Nutrients Tmentioning
confidence: 99%
“…However, if not applied in balance with other cations in the soil, it can compete with Mg 2+ , K + and NH 4+ for the same absorption sites, render the plants deficient in these minerals and unbalance plant nutrition. Studies in this line were carried out in coffee (Garcia Junior et al, 2003), soybean (Pinheiro et al, 2011) and corn (Carvalho et al, 2013).…”
Section: Silicon Influence On the Absorption Of Essential Nutrients Tmentioning
confidence: 99%
“…Indeed, Pinheiro et al (2011) and Doreto et al (2012) observed that excessive potassium fertilization increased the rust progress. Meanwhile, when this nutrient was balanced supplied with other nutrients, such as calcium, a reduction on soybean rust was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have recorded the effects of crop nutrition on rust development (Balardin et al, 2006;Debona et al, 2008;Pinheiro et al, 2011;Doreto et al, 2012). Walters & Bingham.…”
Section: Introductionmentioning
confidence: 99%
“…Isto é, com o aumento do fornecimento dos nutrientes no solo, houve maior absorção pelas plantas. Pinheiro et al (2011), avaliando a influência de doses de K (0, 150, 300, 450 e 600 mg dm -3 ) e de Ca (0,75,150, 225 e 300 mg dm -3 ), na reprodução do nematoide do cisto da soja (Heterodera glycines), também relataram aumento do teor de K com incremento das doses desse nutriente no solo.…”
Section: Nutriçãounclassified